Study on the Occurrence Difference of Functional Groups in Coals with Different Metamorphic Degrees - Jinzhang Jia; Yinghuan Xing; Bin Li; Dan Zhao; Yumo Wu; Yinuo Chen; Dongming Wang (Molecules, 2023)
In order to quantitatively study the difference in occurrence content of functional groups in coals with different metamorphic degrees, the samples of long flame coal, coking coal, and anthracite of three different coal ranks were characterized by FTIR and the relative content of various functional groups in different coal ranks was obtained. The semi-quantitative structural parameters were calculated, and the evolution law of the chemical structure of the coal body was given. The results show that with the increase in the metamorphic degree, the substitution degree of hydrogen atoms on the benzene ring in the aromatic group increases with the increase in the vitrinite reflectance. With the increase in coal rank, the content of phenolic hydroxyl, carboxyl, carbonyl, and other active oxygen-containing groups gradually decreased, and the content of ether bonds gradually increased. Methyl content increased rapidly first and then increased slowly, methylene content increased slowly first and then decreased rapidly, and methylene content decreased first and then increased. With the increase in vitrinite reflectance, the OH-π hydrogen bond gradually increases, the content of hydroxyl self-association hydrogen bond first increases and then decreases, the oxygen-hydrogen bond of hydroxyl ether gradually increases, and the ring hydrogen bond first significantly decreases and then slowly increases. The content of the OH-N hydrogen bond is in direct proportion to the content of nitrogen in coal molecules. It can be seen from the semi-quantitative structural parameters that with the increase in coal rank, the aromatic carbon ratio fa, aromatic degree AR and condensation degree DOC increase gradually. With the increase in coal rank, A(CH2)/A(CH3) first decreases and then increases, hydrocarbon generation potential ‘A’ first increases and then decreases, maturity ‘C’ first decreases rapidly and then decreases slowly, and factor D gradually decreases. This paper is valuable for analyzing the occurrence form of functional groups in different coal ranks and clarifying the evolution process of structure in China.